TAFSIR HERMENEUTIKA INTENSIONALISME DALAM PENERAPAN APLIKASI ATLAS - Sihotang, Ruth Jenny; Mulawarman, Aji Dedi (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2024)
This study aims to determine the meaning of using the Audit Tools and Archives System (ATLAS) application as a financial statement auditing tool, involving Intentional hermeneutics to analyze findings based on historical context, the cultural context in the correlated and explored "text" from which the interpreter tries to interpret the meaning of respective utterances and the language used by the informer utilizing the ATLAS application. Informants in this study include the Managers and Auditor Staff of Thoufan and Rosyid Public Accountants and Partners (Partners) of Achsin Handoko Tomo Public Accounting Firm. The results exhibit that ATLAS presents a complex mapping. The brainchild of ATLAS due to the audit failure cases in Indonesia resulting from a lack of risk assessment/detection in audits has made the Public Accounting Firm implement the ATLAS application. As such, the complexity of the application makes it difficult to implement asthe staffing culture at the Public Accounting Firm causing an imbalance between workload and audit fees for implementing the application.